Pacific finance sector brief Tuvalu. (Metro Manila, Philippines Asian Development Bank, 2019)
The country finance sector consists of two banks, a national provident fund, and a Western Union agent with a handful of small, informal moneylenders. The National Bank of Tuvalu, which has 90% of total banking sector assets, focuses on lending to the household sector and providing home loans, while the Development Bank of Tuvalu supports public and private enterprises. The banking sector in Tuvalu is effectively unregulated and little progress has been made to put in place necessary supervisory and prudential requirements. Key reform priorities are instituting effective banking oversight and expand access to financial services.
Keywords: Finance -- Tuvalu; Industrial policy; Electronic books